IMPLEMENTATION OF THE MICRO BUSINESS CLINIC (KUM) PROGRAM: A PRACTICAL APPROACH EMPOWERING SUSTAINABILITY - Rury Hilda Pandu Winata; Hendra Sukmana (Jurnal Kebijakan Publik, 2025)
This study aims to describe and analyze the implementation of the Micro Business Clinic (KUM) Program in Sidoarjo Regency using a descriptive qualitative research method. The program is designed to support Micro, Small, and Medium Enterprises (MSMEs) by providing consultations, guidance, and financial literacy training. Data collection techniques include observation, interviews, and documentation, with informants selected through purposive sampling. The informants consist of Customer Service staff at the Micro Business Cooperative Clinic and its customers, primarily MSME actors who seek business development assistance. The data analysis follows the Miles & Huberman (1994) model, which includes four stages: data collection, data reduction, data presentation, and conclusion drawing. The research findings highlight four key indicators of program implementation. (1) Communication: The Micro Business Cooperative Clinic actively conducts socialization, workshops, and seminars to educate MSME actors. (2) Resources: The clinic operates with only two human resources, faces budget constraints, and requires additional funding to optimize services. (3) Disposition: The implementation encounters obstacles due to occasional slow performance, impacting service effectiveness. (4) Bureaucratic Structure: The program follows an efficient Standard Operating Procedure (SOP), making it easier for MSME actors to register and access services. Despite its efforts to enhance service quality, the Micro Business Cooperative Clinic continues to face challenges, particularly in terms of human resources and system performance. Addressing these issues is essential to maximize its impact on MSME development in Sidoarjo Regency.